(Dis)connectivity and rural depopulation in Spain: an urgent matter in the age of digital education - Santamaría-Cárdaba, Noelia (2025)
Depopulation in Spanish rural municipalities is an increasingly evident issue; therefore, it is essential to investigate the causes of the drastic decline in inhabitants in these areas. This study specifically aims to verify whether Spanish villages lack digitalization, i.e. whether they have adequate ADSL (Asymmetric Digital Subscriber Line) and LTE (Long-Term Evolution) networks, and to examine the relationship between digital access and depopulation in these areas. The methodology employed focuses on the quantitative analysis of data obtained from secondary sources, specifically the most recent information provided by the Ministry of Economic Affairs and Digital Transformation of the Spanish Government regarding the existing coverage in the municipalities of each province in Castilla and León. The results reveal that rural areas lack adequate ADSL coverage, which may contribute to depopulation as the digital divide in these areas becomes increasingly pronounced.